Automatic extraction of road seeds from high-resolution aerial images - Dal-Poz, Aluir P. [UNESP]; Vale, Giovane M.D.O. [UNESP]; Zanin, Rodrigo B. [UNESP] (FapUNIFESP (SciELO), 2005)
This article presents an automatic methodology for extraction of road seeds from high-resolution aerial images. The method is based on a set of four road objects and another set of connection rules among road objects. Each road object is a local representation of an approximately straight road fragment and its construction is based on a combination of polygons describing all relevant image edges, according to some rules embodying road knowledge. Each one of the road seeds is composed by a sequence of connected road objects, in which each sequence of this type can be geometrically structured as a chain of contiguous quadrilaterals. Experiments carried out with high-resolution aerial images showed that the proposed methodology is very promising in extracting road seeds. This article presents the fundamentals of the method and the experimental results, as well.
Keywords: Digital photogrammetry; Road extraction; Road objects; Road seeds